Overview of Pharmacological Treatment for Gastritis Patients in the Inpatient Unit at RSUD Haji Makassar - Handayani; M. Alfian Rajab; Rindani Claurita Toban (Ammar Dharma Foundation, 2025)
Background: Gastritis is an inflammatory disease of the gastric mucosa with a high prevalence worldwide, particularly in developing countries. Risk factors include Helicobacter pylori infection, diet, stress, and drug use. Pharmacological therapy remains the primary treatment strategy, but drug-related problems may arise. Therefore, evaluating the effectiveness of pharmacological therapy is essential.Objective: This study aimed to evaluate the characteristics of gastritis patients and the effectiveness of pharmacological therapies in reducing pain among inpatients at RSUD Haji Makassar.Methods: A retrospective quantitative descriptive study was conducted using medical records of 76 gastritis patients aged 17–30 years, hospitalized from July to December 2024. Patient characteristics and pharmacological therapy distribution were analyzed. The effectiveness of therapy was assessed by comparing pain scale scores before and after three days of treatment using the Wilcoxon test.Results: Most patients were female (80.3%) and aged 18–24 years (77.6%). The most prescribed drug was Omeprazole (44.7%), followed by Ranitidine (35.5%) and Sucralfate (19.7%). All therapies significantly reduced pain (p < 0.05). Mean pain scores decreased from 4.29 to 0.68 with Omeprazole, from 4.30 to 1.11 with Ranitidine, and from 3.80 to 1.20 with Sucralfate. However, no significant difference was found between treatment groups.Conclusion: Gastritis was more prevalent among young females. Omeprazole was the most frequently used drug, and all three therapies effectively reduced pain after three days. Continuous monitoring is recommended to optimize therapy outcomes.